Cloning of HSP90, expression and localization of HSP70/90 in different tissues including lactating/non-lactating yak (Bos grunniens) breast tissue. - Penggang Liu; Sijiu Yu; Yan Cui; Junfeng He; Chuan Yu; Zexing Wen; Yangyang Pan; Kun Yang; Liangli Song; Xue Yang (PLoS ONE)
The aim of this study is to investigate the expression and localization of HSP70/90 in different tissues and explore the regulation effects of HSP70/90 at lactation period of female yaks. HSP90 mRNA was cloned from the heart samples of female yaks, Quantitative real-time (qRT-PCR), Western blotting (WB), immunohistochemistry and immunofluorescence assays were utilized to analyze the expressions of HSP70/90 mRNA and protein in different tissues. Sequence analysis showed that HSP90 is a conserved molecular chaperone of female yaks. The qRT-PCR, WB results showed that the expressions of HSP70/90 mRNA and protein were significantly different in different tissues, and 3-fold higher expression during the lactation period than the non-lactation period of breast tissue (P < 0.01). Immunohistochemistry and immunofluorescence assays results showed that HSP70/90 were located in the cardiac muscle cells, cerebellar medulla, theca cells lining at the reproductive system, and the mammary epithelia of the breasts. In addition, the expression level of HSP70 was higher than those of HSP90 in all examined tissues. Therefore, our results strongly suggest that the expression and localization of HSP70/90 could provide significant evidence to further research in tissue specific expression, and lactation function of female yaks.